6a-9b=3(2a-3b)
4x-xy=x(4-y)
5ab-5ac=5a(b-c)
3m²-6mn=3m(m-2n)
a^7+a⁴=a⁴(a³+1)
15ab²-5ab=5ab(3b-1)
24x²y+36xy²=12xy(2x+3y)
-4x^8+18x^15=-2x^8(2-9x^7)
3x⁴-6x³+9x^5=3x³(x-2+3x²)
8ab³-12a^7b-24a²b²=4ab(2b²-3a^6-6ab)
18y^5-12xy²+9y³=3y²(6y³-4x+3y)
-14ab³c²-21a²bc²-28a³b²c=-7abc(2b²c+3ac+4a²b)
ab-ac+yb-yc=(ab-ac)+(yb-yc)=a(b-c)+y(b-c)
=(b-c)(a+y)
3x+3y-bx-by=(3x+3y)+(-bx-by)=3(x+y)-b(x+y)=(x+y)(3-b)
4n-nc-4+c=(4n-4)+(-nc+c)=4(n-1)-c(n-1)=
(n-1)(4-c)
x^7-x³+4x⁴-4=(x^7-x³)+(4x⁴-4)=x³(x⁴-1)+4(x⁴-1)=(x⁴-1)(x³+4)
6m²n-3m²+2mn-m=(6m²n-3m²)+(2mn-m)=
3m²(2n-1)+m(2n-1)=(2n-1)(3m²+m)
4a⁴-5a³y-8a+10y=(4a⁴-8a)+(-5a³y+10y)=
4a(a³-2)-5y(a³-2)=(a³-2)(4a-5y)
(a-7)²
(5y+1)²
(10a-9b)²
(4m+7n)²
(x^5-3b)²
(6m³+n^6)²
(1/14x⁴-14y²)²
(9/4a³-2b²)²
9y²-24y+16=9(y-y1)(y-y2)
d=b²-4ac
D=24²-4*9*16=0
y1=y2=24/18=4/3=1 1/3
9y²-24y+16=9*(y-4/3)²=(3y-4)²
<em>IxI=1-b</em>
<em>Если 1-b>0, т.е. b<1, то решений два. ЭТО ±(1-b)</em>
<em>Если b>1, то решений нет.</em>
<em>Если b=1, то х=0- единственное решение.</em>
√2-2sin2x=0
sin2x=√2/2
2x=(-1)^k+πk
x=(-1)^k /2+πk/2
49x^2+140xy+100y^2-ЭТО ОТВЕТ